Promoting sustainable change of smallholders' agriculture in Africa: Policy and institutional implications from a socio-economic cross-country comparative analysis. (15th July 2022) - Branca, Giacomo; Cacchiarelli, Luca; Haug, Ruth; Sorrentino, Alessandro
Abstract: A shift towards sustainable agricultural systems would enhance food security without further depleting natural resources. Considering small-scale farming in the cereal-legume systems of Eastern and Southern Africa, we introduce a conceptual framework and apply an econometric model using data from a sample of 2208 households to assess factors limiting technology diffusion. Results show that investment-ready and food-secure small producers are more willing to adopt agricultural technology options, increased access to financial services is needed to enhance farm households' value-chain readiness and policy interventions promoting pluralistic extension service expansion and enhancing access to stable input and output markets are an incentive to adopt. The results from the cross-country comparison have shown that the examined factors have a similar influence on the extent of farm households' adoption of the proposed agricultural innovations. However, the heterogeneous nature of the smallholder farming environment in Eastern and Southern Africa implies that promotions of sustainable agricultural systems should be based on technology packages adapted to the complexity and diversity of smallholders' farming systems. Highlights: We consider small-scale farming in the cereal-legume systems of Eastern and Southern Africa. An econometric model is applied to assess factors limiting the adoption of improved soil and crop management practices. Findings illustrate common drivers but also differences across countries in agricultural technology adoption. Access to extension services, land, credit, and input and output markets impacts adoption. Our results provide evidence to shape sustainable rural development programs.